(untitled) (World of finance, 2023)
Introduction. The article examines the state of implementation in our country of national legal and organizational-administrative measures provided for the involvement of Ukraine in the common transit procedure in force in the European Union, based on the use of the New Computerized Transit System. The main attention is paid to the legal prerequisites, as well as to the current international and domestic standards, which determine the strategic tasks and their corresponding directions in the organization of the implementation of the joint transit procedure by Ukraine. The set of measures implemented in the process of deployment of the new transit system, which will support effective customs control, promote legal trade and cross-border movement of goods, use modern technologies and meet the requirements of both the customs service of Ukraine and economic operators, has been analyzed. In the conclusions to this article, proposals are formulated regarding the development of the joint transit procedure in Ukraine and further improvement of its functional capabilities. The purpose of the article is to find out the current state of implementation of national legal and organizational and administrative measures aimed at the implementation of the joint transit procedure by Ukraine, with the determination of directions for its further improvement. Methods. The methods of comparison, analysis, and synthesis were used during the study of the state of implementation of national legal and organizational-administrative measures, provided for the involvement of Ukraine in the common transit procedure in force in the European Union (EU). Results. The complex of measures implemented in the process of deployment of the new transit system in accordance with the provisions of international and national standards was characterized, which made it possible to determine and propose directions for promoting the proper functioning and development of the joint transit procedure, in particular, with regard to the further harmonization of national regulatory and legal acts on issues of application, filling out and processing customs declarations in accordance with the provisions of international legislation, improving the variability of the use of transit simplifications, information support for employees of the customs service of Ukraine and economic operators. Perspectives. It is advisable to continue scientific research on the use of the joint transit procedure in Ukraine, taking into account the expected updates of international legal norms regarding the implementation of mutual administrative assistance in relation to requirements, the establishment of rational operational cooperation, coordination and information exchange with other customs organizations, including for the purpose of managing transit operations and their tracking.